Prevalence of depression, anxiety and suicidal ideas and associated factors, in particular sensory impairments, in a population of Bashkortostan in Russia - Bikbov, Mukharram; Gilmanshin, Timur R.; Kazakbaeva, Gyulli M.; Iakupova, Ellina M.; Panda-Jonas, Songhomitra; Zainullin, Rinat M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Gilemzianova, Leisan I.; Khakimov, Dinar A.; Miniazeva, Liana A.; Jonas, Jost B. (Scientific reports, 2023)
To assess prevalence and associated factors of depression, anxiety and suicidal ideas in populations from Russia, we conducted in rural and urban regions in Bashkortostan/Russia two population-based studies (Ural Eye and Medical Study (UEMS), performed from 2015 to 2017; Ural Very Old Study (UVOS), performed from 2017 to 2020) which included participants aged 40 + years and 85 + years, respectively. Depression was assessed using the questionnaire of the Center for Epidemiologic Studies Depression Scale Scoresheet, and anxiety was examined applying the State Trait Inventory Anxiety Test. Suicidal ideas were explored by the question whether suicide had previously been thought of or attempted (and if yes, for what reasons). In the statistical analysis we assessed the mean of the main outcome parameter (depression score and anxiety score) and searched for associations between these parameters and other parameters in univariable and multivariable regression analyses. In the UEMS with 5893 individuals (age: 59.0 ± 10.7 years; range 40-94 years), higher depression score and anxiety score were associated (multivariable analysis) with more marked hearing loss (beta: 0.07; P < 0.001, and beta: 0.07; P < 0.0012, respectively) and worse visual acuity (beta: 0.04; P = 0.02; and beta: 0.03; P = 0.03, resp.), in addition to female sex, Russian ethnicity, lower educational level, less alcohol consumption, weaker hand grip strength, less physical activity, and higher prevalence of dry eye disease. Attempted suicide was reported by 88 (1.5%; 95% CI 1.2, 1.8) participants. Having thought of suicide within the last 6 months was reported by 63 (1.1%) individuals. Out of 1491 UVOS participants (age: 88.2 ± 2.8 years; range 85-100 years) with a mean depression score of 20.0 ± 10.3 (median 18; range 0-58), 916 (61.4%; 95% CI 59.0, 63.9) fulfilled the definition of depression (depressions core ≥ 16). Higher depression score and higher anxiety score correlated (multivariable analysis) with higher hearing loss score (beta: 0.07; P = 0.02, and beta: 0.08; P = 0.009, resp.) and worse visual acuity (beta: 0.13; P < 0.001, and beta: 0.09; P = 0.007, resp.), in addition to female sex, urban region, less physical activity, less fruit intake, and lower cognitive function. Overall, 15 (1.0%; 95% CI 0.50, 1.50) individuals had attempted or thought of suicide. In conclusion, the findings suggest that besides female sex, lower level of education and lower cognitive function, it was sensory impairment, namely vision and hearing impairment, which belonged to the determinants of depression and anxiety in these populations from Russia.
Gesehen am 17.06.2024